Determinants of procurement strategy for construction works: quantity surveyors’ perspectives - Olanrewaju, AbdulLateef; Anavhe, Paul Junior; Abdul Aziz, Abdul Rashid; Chu, Hui Chen; Wai, Soon Han (EDP Sciences, 2016)
The selection of the ‘appropriate’ procurement strategy is a prerequisite to the success or failure of a construction project. This paper investigates the factors determining the selection of appropriate procurement strategy for construction works in Nigeria. Data for the study was collected through an online survey questionnaire. The survey administration involves only quantity surveyors. Quantity surveyors were targeted because they advise clients and other stakeholders on procurement and contractual issues on construction works. A total of 33 usable responses were received and analysed for this study. On the basis of the results, it is concluded that the selection of procurement strategies for construction depend on complex interrelated factors. The study could not detect a particular factor or few factors responsible for a procurement strategy selection. The findings of this study is useful because it argues that the construction sector needs to broaden its considerations on the procurement strategy’s determinants rather than focusing solely on the client’s type and nature of projects as is often cited. Future research could segment these factors in terms of class of construction works or increase the sample size, which might lead to different findings.